Effects of Tocilizumab on Adults With COVID-19 Pneumonia: A Meta-Analysis - Chen, Chi-Chung; Yang, Yu-Pei; Tsai, Hsien-Lung; Tung, Tao-Hsin (Frontiers in Medicine, 2022)
Background：COVID-19, a worldwide disaster, already affected lots of people. Effective care and therapy are currently being evaluated in full swing. Purpose：Our purpose was to investigate the effects of tocilizumab, an interleukin-6 receptor inhibitor, on treating adult patients with COVID-19 pneumonia. Data sources, study selection and data extraction：We conducted a meta-analysis and searched for relevant studies on PubMed, Embase, and the Cochrane library without restrictions on language from inception until 1 February 2021. Fifteen studies were included for this meta-analysis. Two authors independently selected and screened these studies, assessed the quality of including studies and extracted relative information. Results：Fifteen studies were included in this meta-analysis. The main studies showed that tocilizumab was associated with lower mortality (risk ratio=0.62, 95% confidence interval=0.46-0.83 and hazard ratio=0.61, 95% confidence interval=0.51-0.72). Using tocilizumab might also affect the biochemistry indicators (lowered C-reactive protein, ferritin, increased lymphocyte count). Conclusions：These current evidences could indicate that early using of tocilizumab was associated with lower mortality in COVID-19 adult patients. Early using of tocilizumab could reduce the mortality rate of adult patients with COVID-19 without obvious fatal side effects, which may be a treatment option in patients with COVID-19 pneumonia.